Potassium Supplying Capacity of Neyattinkara- Vellayani soil Association and its Relationship with Potash Nutrition of Major Crops on Them - Valsaji K (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 1989)
Detailed study on the potassium supplying capacity of Neyattinkara-Vellayani soil association and its relationship to potash nutrition of major crops on them namely coconut and cassava has been made. This soil association represents the red loam soil type and consists of Neyattinkara series tentatively classified under Typic Eutropepts and Vellayani series under Typic Tropudalfs. Soil samples were collected from selected fields under coconut and cassava for the dominant soil types namely sandy clay loam and sandy loam soils under Neyattinkara and Vellayani series. To find the most suitable depth and location of soil sampling for coconut samples were also drawn at two different depths of 0-30 and 30-60 cm from basins and interrows. Empirical methods, quantity intensity studies, electro ultrafiltration studies and foliar diagnostic techniques were employed to decide on the most suitable method for plant available K. The various intensity, quantity and capacity factors which relate the readily available, difficultly available and storage or buffer capacity were assessed for a proper appraisal of the K status and supplying capacity. The various soil K parameters such as total K, water soluble K, exchangeable K, available K, nonexchangeable K, HNO3 extractable K, H2SO4 extractable K, sodium tetraphenylboron extractable K and percentage K saturation were found to be low. The water soluable K formed higher proportion of available K than exchangeable K. Interrelations showed that water soluble K, exchangeable K and available K are in dynamic equilibrium. Nonexchangeable K did not show any relationship with available K indicating that it is a poor source of available K. Quantity-intensity studies showed that the shape of the Q/I curve was similar in all types of soil since they belong to a group of related soils. The Q/I parameters like Are.K, Ko, Kx. KL and potential buffering capacity values were low. The KL values were higher than NH4OAc.K. The free energy values were found to be high indicating easy release rates of K. For both coconut and cassava, the leaf K did not show any consistent relationship with the soil K parameters. Among the Q/I parameters, KL had significant relation with leaf K of coconut. EUF 10 and EUF 35 showed significant relationship with leaf K of both coconut and cassava. Electro-ultrafiltration studies showed that the easily desorbed K was more than the strongly desorbed K indicating easy supply rate. The EUF 30-35 values were related to HNO3.K showing that this fraction included some initially nonexchangeable K. EUF 10 had significant relation with exchangeable K and EUF 35 had significant relation with exchangeable and available K. The buffer parameters BK (EUF 10/EUF 30) and EUF.Q (EUF 30-35/EUF 30) values were low indicating low buffer capacity. The EUF desorption pattern showed that the first peak was within 10-20 minutes and prominent than the second peak. This indicated low reserve K but easy supply rates. The EUF desorption curve of soils with high NH4OAc.K was above that of soils with low NH4OAc.K. This indicated that with increase in NH4OAc.K the easily desorbed K also increased. The yield of coconut and cassava were related to the various K parameters to evaluate the suitability of different methods for available K. In most of the cases NH4OAc method was found to be suitable for both coconut and cassava. Leaf analysis was also found to be suitable. For cassava the result obtained after 41/2 months is meaningless for the current crop. For coconut collection of index leaf is laborious. It was also found that the Q/I and EUF were suitable for coconut. But these methods cannot be followed in routine soil testing because of the high input of laboratory work involved. Considering these aspects it was found that NH4OAc method is the most suitable one because it is simple, cheap and easy to adopt. Based on the NH4Ac.k content the fertility status was found to be low to medium. The various intensity, quantity and capacity factors of soil K, Q/I and EUF parameters revealed that this soil association has low K supplying capacity. Hence heavy dose of K fertilizers is required. Split application is preferable especially in sandy loam soils to reduce leaching losses. NH4OAc.K which was found as a suitable indicator of plant available K varied significantly in basin and inter-row samples of sandy clay loam soils. This K fraction did not vary with depth in both sites. In general, the K nutrient index indicated that the basin samples had a higher level than inter-row and surface samples. Thus basin sampling at 0-30 cm depth was found to be the ideal site of soil sampling for coconut tree.